THE IMPACT OF LEARNING MANAGEMENT SYSTEMS ON STUDENT ACHIEVEMENT AND ENGAGEMENT IN ONLINE CLASSROOMS - Pesovski, Ivica; Klashninovski, A; Makeska, A M; Trajkovik, Vladimir (IATED, 2022)
Online learning was the solution that saved the educational system from collapsing after the pandemic outburst. Students and teachers at all levels of education were pushed to switch from face-to-face to remote learning and teaching. This paper analyzes the effects that learning management systems have on students’ engagement and achievement during their studies. The activities that were measured are class attendance, scores on weekly tasks and scores on monthly projects. This study involves a total of 169 students who participated in a year-long intensive computer programming course. The first group of 66 students began the course in April 2020 by attending online classes while the entire course programme was managed manually in excel sheets. The second group of 106 students began the course in October 2020 and all their activities were measured automatically using a custom-build learning management system. The learning management system centralized many aspects of the student’s journey, like visiting classes, watching recorded class videos, taking exams, receiving feedback and competing with their peers via leaderboards. The results show that there is not much difference between students’ achievement and engagement before and after implementing the learning management system. Having leaderboards to compete with their friends, did not excite students enough in order to be more competitive and drastically improve their engagement. Learning management systems seem to be more beneficial for the educational institutions providing them as they store all the data in one place, data which they can analyze and use to make educated decisions for improving the study programme and nurture the student’s motivation.
Keywords: Online learning, student engagement, student performance, learning management systems